Regulation of Gamma-Aminobutyric Acid Transaminase Expression and Its Clinical Significance in Hepatocellular Carcinoma - Gao, Xiaoqiang; Jia, Xiaodong; Xu, Moyan; Xiang, Jiao; Lei, Jin; Li, Yinyin; Lu, Yinying; Zuo, Shi (Frontiers in Oncology, 2022)
Background: Gamma-aminobutyric acid transaminase (ABAT) catalyzes the conversion of gamma-aminobutyric acid (GABA) into succinic semialdehyde. Although some evidence supports a key role of ABAT in the progression of hepatocellular carcinoma (HCC), no systematic analysis is available. Thus, this study aimed to investigate the possible mechanisms related to low ABAT expression and the prognostic value and potential functions of ABAT in HCC. Methods: We obtained relevant datasets from the Encyclopedia of RNA Interactomes, MethSurv, cBioPortal, TISIDB and The Cancer Genome Atlas and used bioinformatic methods to analyze DNA methylation, copy number variation, gene mutation, and upstream microRNAs (miRNAs) of ABAT, exploring the potential relationship between ABAT expression and the prognosis, glycolysis, and immune infiltration in HCC. Results: The results indicated that ABAT expression was lower in HCC tumor tissues than in normal tissues or adjacent tissues. Low ABAT expression was related to patient age, T stage classification, pathologic stage, histological grade, and alpha-fetoprotein level of HCC. Kaplan-Meier survival analyses indicated that low ABAT expression was correlated with poor HCC prognosis. ABAT was also verified as an independent risk factor in HCC via Cox multivariate analysis. Gene set enrichment analysis showed enrichment in various signaling pathways. Furthermore, DNA methylation, copy number variation, and gene mutation potentially induced low ABAT expression; miR-135a-5p was a potential upstream miRNA of ABAT. Additionally, ABAT expression was associated with glycolysis-related genes, infiltrated immune cells, immunoinhibitors, and immunostimulators in HCC. Conclusions: Our study reveals that deficient ABAT expression is correlated with disease progression and poor prognosis in HCC because of its role in tumorigenesis and tumor immunity.